The regulation role and diagnostic value of fibrinogen-like protein 1 revealed by pan-cancer analysis. (15th December 2022) - Yi, Wanwan; Qiao, Tingting; Yang, Ziyu; Hu, Lei; Sun, Mingming; Fan, Hengwei; Xu, Yanping; Lv, Zhongwei
Abstract: Although the role of fibrinogen-like protein 1 (FGL1) in tumorigenesis is well known, a pan-cancer analysis of FGL1 lacks. We used bioinformatics techniques to analyze cancer data from publicly available datasets from The Cancer Genome Atlas, UALCAN, TIMER, Gene Expression Profiling Interactive Analysis, cBioPortal, Search Tool for the Retrieval of Interacting Genes, and DAVID. FGL1 expression was significantly regulated in various common tumors than in normal tissues; it was increased in lung adenocarcinoma and decreased in colon adenocarcinoma. Cox regression analysis demonstrated that the upregulation of FGL1 expression was correlated with poor overall survival (OS) and disease-free survival (DFS) in stomach adenocarcinoma, brain low-grade glioma, cervical squamous cell carcinoma, and endocervical adenocarcinoma. Decreased FGL1 methylation levels were observed in majority of tumor types. FGL1 expression was significantly associated with the levels of immune cell subtypes and immune checkpoint genes. Deep deletion was the most common genetic mutation in FGL1 that led to frame-shift mutations, which was closely associated with poor progression-free interval, disease-specific survival, and OS in patients with FGL1 mutations. Kyoto Encyclopedia of Genes and Genomes enrichment analysis showed that FGL1 -related genes participate in diverse pathways. Ubiquitin-mediated proteolysis is significantly correlated to the function of FGL1, which was identified for the first time in the present study. This pan-cancer study provides a deep understanding of the functions of FGL1 in progression of many tumors and demonstrates that FGL1 may be a potential biomarker for the diagnosis, prognosis, and immune infiltration in cancer. Graphical abstract: Image 1